2015
DOI: 10.1890/es14-00316.1
|View full text |Cite
|
Sign up to set email alerts
|

The cascading impacts of livestock grazing in upland ecosystems: a 10‐year experiment

Abstract: Abstract. Livestock grazing is a major driver of land-use change, causing significant biodiversity loss globally. Although the short-term effects of livestock grazing on individual species are well studied, a mechanistic understanding of the long-term, cascading impacts is lacking. We manipulated livestock densities using a unique, replicated upland experiment over a 10-year period and found significant effects of grazing treatment on plant and arthropod biomass; the number of Anthus pratensis breeding bird te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 45 publications
1
63
0
5
Order By: Relevance
“…Regarding cattle, their presence on sea walls can create very short, homogeneous grassland swards (uniformly <10 cm height) which reduces suitability for Orthoptera (Gardiner et al 2015). Eventually, modifying grassland ecosystems with domestic livestock grazing can lead to a significant loss of biodiversity (Evans et al 2015). On Essex sea walls in Eastern England, Orthoptera were recorded from 2 x 2 m quadrats (5 quadrats per plot) in cattle, sheep and rabbit grazed grassland plots and compared to mown plots using a one-way analysis of variance (ANOVA) after square-root transformation of count data to normalize it.…”
Section: Livestock Effects On Orthopteramentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding cattle, their presence on sea walls can create very short, homogeneous grassland swards (uniformly <10 cm height) which reduces suitability for Orthoptera (Gardiner et al 2015). Eventually, modifying grassland ecosystems with domestic livestock grazing can lead to a significant loss of biodiversity (Evans et al 2015). On Essex sea walls in Eastern England, Orthoptera were recorded from 2 x 2 m quadrats (5 quadrats per plot) in cattle, sheep and rabbit grazed grassland plots and compared to mown plots using a one-way analysis of variance (ANOVA) after square-root transformation of count data to normalize it.…”
Section: Livestock Effects On Orthopteramentioning
confidence: 99%
“…Increasing grazing intensity may affect trophic levels by negatively affecting both primary and secondary consumers (Ma et al 2017). Removal of vegetation biomass by grazing negatively affects herbivorous arthropod abundance and consequently reduces predator numbers, especially of the field vole Microtus agrestis L., 1761 (Rodentia: Cricetidae; Evans et al 2015). In a ten-year experiment, Evans et al (2015) suggested that intense long-term ungulate grazing can have an important impact on trophic levels but not on plant diversity.…”
Section: Livestock Effects On Orthopteramentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep grazing has a profound effect on vegetation, with important knock-on effects on animal communities and ecosystems (Evans et al 2015). Longer term effects of grazing on Milne, pers.…”
Section: Aspects Of Sustainability In Sheep Grazing Management Biodivmentioning
confidence: 99%
“…However, many studies point to overall benefits to biodiversity from a reduction in sheep grazing intensity. Low-intensity mixed grazing by sheep and cattle (equivalent to 0.91 ewes ha −1 ) was identified as providing optimal biodiversity benefits in the Scottish uplands by maintaining vole populations, a key prey species for raptors and other vole-eating invertebrates (Evans et al 2006a(Evans et al . 2015.…”
Section: Aspects Of Sustainability In Sheep Grazing Management Biodivmentioning
confidence: 99%